A sociedade da informação no Brasil: um ensaio sobre os desafios do Estado - FERREIRA, Rubens da Silva (2014)
This article treats of the challenges the State faces for consolidating an information society in Brazil. These challenges are illiteracy, the need of developing human resources and the difficulty of any citizen in accessing information technology. Information society is understood as something ambivalen for the Brazilian State. It represents challenges but at the same time opportunities for developing an informational order, characterized by very quick changes in a contemporary society. Therefore, the State has to elaborate and apply relevant public policies for overcoming these challenges in order to build up a more evenly accessible information society in Brazil.